Evolutionary relationships among six closely related subfamilies of the braconidae (hymeniptera),inferred from 28s and nadhi markers. - Yaakop, S; Van Achterberg, C; Idris , A.B (Pusat Sistematik Serangga ,UKM, 2010)
The phylogenetic relationships among six closely related subfamilies of the braconenidae,i.e alysiinae,braconinae (braconini)exothecinae, gnamptodontinae,opiinae and rogadinae (rogadini) were investigated using 28s and NADH1 sequences data,mostly on the Malaysian species. This study was also attempted to confirm the relationships of the exothecinae and gnamptodontinae with the alysiinae/opiinae lineage by using NADH1 sequences.Result showed that the exothecinae subfamily was closely related to the alysiinae/opiinae lineage than the gnamptodontinae. The alysiinae and opiinae formed amonophyletic-group only based on the 28s sequences data while the roganidae(rogadini)and braconidae (braconini) were found to be less derived subfamiles. The evalutionary transitions of the biological strategist for six subfamilies were also presented. This study was attempted to confirm the relationships of the exothecinae and gnamptodontinae with the alysiinae/opiinae lineage by using NADH1 sequences. The position of the exothecinae, as a closer subfamily to the sister-group,alysiinae+opiinae than the gnamptodontinae was confirmed wich also supported by the biological data.